Industrial IoT devices and cyber-physical production systems: review and use case - Rúbio, Eva Masero (2020)
“This is a post-peer-review, pre-copyedit version of an article published in Lecture Notes in Electrical Engineering. The final authenticated version is available online at: https://doi.org/10.1007/978-3-319-91334-6_40"